DESCRIPTION OF MANAGEMENT COMPETENCE IN PHYSICAL EDUCATION AND SPORTS STUDENTS (Scientific journal of the Fergana State University, 2023)
This article focuses on concerns associated with insufficient preparation of organizational and managerial competencies in the field of physical education and sports. Research has shown that students, particularly graduates, have an increased propensity to take on leadership roles in sports organizations, although this trend is less pronounced among women, highlighting the move towards competency-based education to improve and assess the development of management skills.